An Empirical Study on Factors Affecting Satisfaction and Loyalty with Independent Institutions Among Vocational Students in Sichuan, China - Liu, Yao (Scholar: Human Sciences, 2024)
Purpose: The objective of this study is to examine the factors that affect students’ satisfaction and loyalty towards independent institutions in Chengdu, Sichuan province. The conceptual model incorporates seven variables which are perceived value, service quality, university reputation, university image, and student trust on student satisfaction and student loyalty. Research design, data, and methodology: A quantitative approach was employed, and a questionnaire was utilized to collect data from the targeted population. The study involved 578 vocational undergraduate students from four selected independent institutions in Chengdu. Prior to distributing the questionnaire, the content validity and reliability were assessed through Item-Objective Congruence and Cronbach’s Alpha pilot test. Sampling methods include judgmental, quota and convenience sampling. The data were analyzed using Confirmatory Factor Analysis and Structural Equation Modeling to validate the model’s goodness of fit and establish the causal relationship among variables for hypothesis testing. Results: The findings revealed that perceived value, university reputation, and university image significantly affect student satisfaction. Moreover, the study demonstrated that student satisfaction is the significant antecedents of student loyalty and perceived value. However, service quality and student trust have no significant effect on student satisfaction. Conclusions: Significant government support is essential to promote the development and improvement of independent institutions to enhance student satisfaction and loyalty.